Evaluation of the immunogenic capability of the BCG strains BCGΔBCG1419c and BCGΔBCG1416c in a three-dimensional human lung tissue model. Issue 14 (27th March 2018) - Parasa, Venkata Ramanarao; Rose, Jeronimo; Castillo-Diaz, Luis Alberto; Aceves-Sánchez, Michel de Jesús; Vega-Domínguez, Perla Jazmín; Lerm, Maria; Flores-Valdez, Mario Alberto
Highlights: Early granuloma formation does not change in response to deletion of BCG1416c or BCG1419c . Deletion of BCG1419c increases IL-6 and MCP-1 production in a 3D human lung tissue model. IL-6 increase in the 3D human lung tissue model driven by BCGΔBCG1419c resembles activation promoted by M. tuberculosis . Abstract: Tuberculosis (TB) still remains as an unmet global threat. The current vaccine is not fully effective and novel alternatives are needed. Here, two vaccine candidate strains derived from BCG carrying deletions in the BCG1416c or BCG1419c genes were analysed for their capacity to modulate the cytokine/chemokine profile and granuloma formation in a human lung tissue model (LTM). We show that the clustering of monocytes, reminiscent of early granuloma formation, in LTMs infected with BCG strains was similar for all of them. However, BCGΔBCG1419c, like M. tuberculosis, was capable of inducing the production of IL-6 in contrast to the other BCG strains. This work suggests that LTM could be a useful ex vivo assay to evaluate the potential immunogenicity of novel TB vaccine candidates.